Factors that contribute the job satisfaction among staff at KPTMBKB waterfront campus / Wan Nurul 'Ain Wan Zolkarnani - Wan Zolkarnani, Wan Nurul 'Ain (2012)
The aim of this study is to examine the factors that influence employee’s job satisfaction at Kolej Poly-Tech MARA Lembah Sireh, Kota Bharu. There are four factors that have been studied, which are: salary, working environment, task given and job training. In collecting data, the researcher used both secondary and primary data. The questionnaires had been used in order to get feedback from the staff. Researcher had distributed 100 questionnaires randomly to 199 staff at KPTM Lembah Sireh. Out of 100, 50 questionnaires was return back. The data collected was tested on its frequency analysis. Further analysis had been done by using reliability analysis. Correlation was used to test the hypotheses in this study as well as regression analysis. The findings of this study show that all independent variables which are salary, working condition, task given and job training have relationship with the job satisfaction amongst employees at KPTM. Out of four factors, three factors which are salary, task given and job training positively influence the job satisfaction of employees at KPTM Lembah Sireh. Another one factors which is working condition not influence the job satisfaction amongst employees at KPTM Lembah Sireh. From the result obtained in this study, researcher suggests some recommendations that can help KPTM Lembah Sireh to improve their employees job satisfaction